Comparison of an enzyme immuno assay (Antigenz Chlamydia) with cell culture for the detection of genital chlamydial infection in high and low risk populations. Issue 2 (April 1993) - Mumtaz, G; Clark, S; Ridgway, G L; Miller, C J; Johal, B; Allason Jones, E
Abstract : OBJECTIVE–To evaluate a new enzyme immuno assay, Antigenz Chlamydia, for the detection of chlamydial antigen in urogenital samples using cell culture as the gold standard for comparison and direct immuno fluorescence to aid resolving the discrepancies. SUBJECTS–212 men and 303 women attending an STD clinic and 404 women of child bearing age attending gynaecological clinics. RESULTS–Sensitivity, specificity, predictive value of positive result and predictive value of negative result of the new test were 77.6%, 99.0%, 94.3%, and 95.7% respectively in the high risk population with a prevalence of 16.5%. In the low risk population the figures were 84.2%, 94.5%, 43.2% and 99.2% respectively with a prevalence of 4.7%. CONCLUSION–Antigenz Chlamydia is an easy and quick test to perform. The test is suitable for use in high risk and low risk populations provided all positive samples are confirmed.